Peter Blau y Otis Dudley Duncan. The american occupational structure. Nueva York : John Wiley and Sons, 1967. 520 p. - Reyna, Jose Luis (Estudios Demográficos y Urbanos, 1968)
PETER BLAU Y OTIS DUDLEY DUNCAN, The American Occupational Structure. Nueva York, John Wiley and Sons, 1967.